Multi-path Solutions to Improve Network Performance - Arzani, Behnaz (Network Protocols (ICNP), 2014 IEEE 22nd International Conference on, 2014)
Multi-path Solutions to Improve Network Performance Behnaz Arzani With the increasing number of internet users, providing performance guarantees to these users is becoming increasingly difficult. In wireless settings, the problem of providing network performance guarantees is even more difficult due to variabilities in link characteristics. Changes in wireless link performance, such as packet loss rate, occur at shorter time scales compared to their wired counterparts. Thus, the finite reaction time of traditional solutions, eg Routing, make them unreliable in mitigating the impact of these variations on user performance. Such variability in the delivered rates could be detrimental to particular types of applications such as video and audio which are sensitive to short term variations.